High-Performance ZnO Transistors Processed Via an Aqueous Carbon-Free Metal Oxide Precursor Route at Temperatures Between 80-180 °C - Lin, Yen-Hung; Faber, Hendrik; Zhao, Kui; Wang, Qingxiao; Amassian, Aram; McLachlan, Martyn; Anthopoulos, Thomas D. (Advanced materials (Weinheim), 2013)
An aqueous and carbon‐free metal‐oxide precursor route is used in combination with a UV irradiation‐assisted low‐temperature conversion method to fabricate low‐voltage ZnO transistors with electron mobilities exceeding 10 cm2/Vs at temperatures <180 °C. Because of its low temperature requirements the method allows processing of high‐performance transistors onto temperature sensitive substrates such as plastic.